Connecting networks companion guide - Cisco Networking Academy (Indianapolis : Cisco Press, 2014)
As the only Cisco-authorized Companion Guide, Connecting Networks Companion Guide is an indispensable resource for the official Cisco Networking Academy Connecting Networks course. Hundreds of thousands of Cisco Networking Academy students worldwide have benefitted from this portable desk reference. It is ideal for studying anytime and anywhere! Connecting Networks Companion Guide is fully aligned to the online course chapters. It offers additional book-based pedagogy to reinforce key concepts, enhance your comprehension of the material, and to promote retention. Using this Companion Guide, you can focus scarce study time, organize review for quizzes and exams, and get the day-to-day reference answers that you are looking for. A full-featured textbook with chapter content that aligns 1:1 with the online course topics, this instructional tool will fully prepare you for quizzes and exams, then further serve as a future reference resource. There will be a Glossary in the back of the book containing Key Terms